Stability by assigning structures by applying the multivariable subspace identification algorithm for a wind system with a DFIG - Fernando Mesa; Germán Correa Vélez; José José Barba Ortega (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In this paper, a controller for a doubly fed induction generator (DFIG) connected to a wind system is proposed. This control assigning its own structures as an optimal control method, the electric model in the DFIG state space is also shown, for which it is expected to estimate a linear model through the subspace technique and thus to design the controller. It will be possible to show that a structure assignment controller is undoubtedly a good option for the control of multivariable systems. The results of the output signals will be analyzed when applying the controller, assigning their own structures, which will allow us to observe that the response and disturbance times are below two tenths of a second.